Influence of systematic variations of the stimulation profile on responses evoked with a vestibular implant prototype in humans. (12th June 2020) - Crétallaz, Céline; Boutabla, Anissa; Cavuscens, Samuel; Ranieri, Maurizio; Nguyen, T A Khoa; Kingma, Herman; Van De Berg, Raymond; Guinand, Nils; Pérez Fornos, Angélica
Abstract: Objective. To explore the impact of different electrical stimulation profiles in human recipients of the Geneva-Maastricht vestibular implant prototypes. Approach. Four implanted patients were recruited for this study. We investigated the relative efficacy of systematic variations of the electrical stimulus profile (phase duration, pulse rate, baseline level, modulation depth) in evoking vestibulo-ocular (eVOR) and perceptual responses. Main results. Shorter phase durations and, to a lesser extent, slower pulse rates allowed maximizing the electrical dynamic range available for eliciting a wider range of intensities of vestibular percepts. When either the phase duration or the pulse rate was held constant, current modulation depth was the factor that had the most significant impact on peak velocity of the eVOR. Significance. Our results identified important parametric variations that influence the measured responses. Furthermore, we observed that not all vestibular pathways seem equally sensitive to the electrical stimulus when the electrodes are placed in the semicircular canals and monopolar stimulation is used. This opens the door to evaluating new stimulation strategies for a vestibular implant, and suggests the possibility of selectively activating one vestibular pathway or the other in order to optimize rehabilitation outcomes.